Comparison between D-loop methylation and mtDNA copy number in patients with Aicardi-Goutières Syndrome - Dragoni, Francesca; Garau, Jessica; Orcesi, Simona; Varesio, Costanza; Bordoni, Matteo; Scarian, Eveljn; Di Gerlando, Rosalinda; Fazzi, Elisa; Battini, Roberta; Gjurgjaj, Altea; Rizzo, Bartolo; Pansarasa, Orietta; et al. (Frontiers in Endocrinology, 2023)
Aicardi-Goutières Syndrome (AGS) is a rare encephalopathy with early onset that can be transmitted in both dominant and recessive forms. Its phenotypic covers a wide range of neurological and extraneurological symptoms. Nine genes that are all involved in nucleic acids (NAs) metabolism or signaling have so far been linked to the AGS phenotype. Recently, a link between autoimmune or neurodegenerative conditions and mitochondrial dysfunctions has been found. As part of the intricate system of epigenetic control, the mtDNA goes through various alterations. The displacement (D-loop) region represents one of the most methylated sites in the mtDNA. The term "mitoepigenetics" has been introduced as a result of increasing data suggesting that epigenetic processes may play a critical role in the control of mtDNA transcription and replication. Since we showed that RNASEH2B and RNASEH2A-mutated Lymphoblastoid Cell Lines (LCLs) derived from AGS patients had mitochondrial alterations, highlighting changes in the mtDNA content, the main objective of this study was to examine any potential methylation changes in the D-loop regulatory region of mitochondria and their relationship to the mtDNA copy number in peripheral blood cells of AGS patients with mutations in various AGS genes and healthy controls. We collected blood samples from 25 AGS patients and we performed RT-qPCR to assess the mtDNA copy number and pyrosequencing to measure DNA methylation levels in the D-loop region. Comparing AGS patients to healthy controls, D-loop methylation levels and mtDNA copy number increased significantly. We also observed that in AGS patients, the mtDNA copy number increased with age at sampling, but not the D-loop methylation levels, and there was no relationship between sex and the mtDNA copy number. In addition, the D-loop methylation levels and mtDNA copy number in the AGS group showed a non-statistically significant positive relation. These findings, which contradict the evidence for an inverse relationship between D-loop methylation levels and mtDNA copy number, show that AGS patients have higher D-loop methylation levels than healthy control subjects. Additional research is needed to identify the function of these features in the etiology and course of AGS.